Rhetorical evolution of oppositional discourse in French academic writing. Oppositional discourse in academic writing - Salager-Meyer, Françoise (HERMES - Journal of Language and Communication in Business, 2000)
We here analyze the quantitative and qualitative evolution of academic conflict (AC) in a corpus of 90 medical articles published between 1810 and 1995. The linguistic means expressing AC were recorded in each paper and classified according to whether they expressed a direct or an indirect conflict.  The frequency of each category of AC was first recorded in each paper, and then calculated per 20–year periods. Our results were analyzed using Chi–square tests. In the whole corpus, direct AC were more frequent than indirect ones (p = .0001). When analyzed per 20–year periods, our quantitative results allowed us to divide the 185 years studied into 2 distinct periods, the cutting–off point being the 1910’s when the frequency of indirect AC started a slow but continuous ascent. In each Block direct AC outnumbered indirect ones (p =.0001), but indirect AC were more frequent in Block B than in Block A (p = .039). A qualitative analysis of the AC recorded revealed that both 19th and 20th century AC were expressed in a personal, polemical and authoritarian manner, although the confrontational stance of late 20th century AC tends to be mitigated either by means of hedging expressions or through the shifting of person to object thematization. We conclude that when formulating their professional disagreement, French-speaking scientists have always been authoritative, categorical, direct and personal, although the tone of voice of confrontations tends to be more “low key” as we approach the turn of the 21st century.